2022
DOI: 10.1007/s11154-022-09718-9
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-guided detection of pituitary neuroendocrine tumor (PitNET) tissue during endoscopic transsphenoidal surgery available agents, their potential, and technical aspects

Abstract: Differentiation of pituitary neuroendocrine tumor (PitNET) tissue from surrounding normal tissue during surgery is challenging. A number of fluorescent agents is available for visualization of tissue discrepancy, with the potential of improving total tumor resection. This review evaluates the availability, clinical and technical applicability of the various fluorescent agents within the field of pituitary surgery. According to PRISMA guidelines, a systematic review was performed to identify reports describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…Their results displayed that 12/15 gliomas were visualized with the NIRF imaging, with a sensitivity of 98% and specificity of 45% to confirm malignant areas in gadolinium-enhancing specimens. Similar results were later validated in brain metastases ( 24 ), pituitary adenomas ( 26 ), and intracranial meningiomas ( 21 ), pulmonary metastasectomy ( 23 ), breast lumpectomy ( 28 ) and other malignant tumors, in which the doses of ICG have varied between 5 mg/kg to 2.5 mg/kg. Newton et al ( 22 ) stratified patients by tumor histology and investigated the optimal dose of ICG in second window technique.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Their results displayed that 12/15 gliomas were visualized with the NIRF imaging, with a sensitivity of 98% and specificity of 45% to confirm malignant areas in gadolinium-enhancing specimens. Similar results were later validated in brain metastases ( 24 ), pituitary adenomas ( 26 ), and intracranial meningiomas ( 21 ), pulmonary metastasectomy ( 23 ), breast lumpectomy ( 28 ) and other malignant tumors, in which the doses of ICG have varied between 5 mg/kg to 2.5 mg/kg. Newton et al ( 22 ) stratified patients by tumor histology and investigated the optimal dose of ICG in second window technique.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, second window ICG (SWIG) technique based on the enhanced permeability retention (EPR) effect was put forward to improve tumor background ratios (TBRs) by altering the time and dose of ICG injection ( 18 , 19 ). Nowadays, SWIG approach of high-dose (2.5 mg/kg-5 mg/kg) ICG intravenous infused 24 h prior to surgery has been widely attempted in intraoperative NIRF imaging for identifying tumor margins or discriminating occult cancerous lesions ( 19 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent label-based guidance may improve resection by selectively causing tumor tissue to fluoresce, assisting visualization and resection. Studies have shown conflicting results among the available fluorescent agents ( 19 , 29 ). Sodium fluorescein (FNa) and 5-ALA with laser-based optical biopsy are two agents that have been shown to selectively fluoresce adenomatous tissue; however, these results are not consistent across all studies ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown conflicting results among the available fluorescent agents ( 19 , 29 ). Sodium fluorescein (FNa) and 5-ALA with laser-based optical biopsy are two agents that have been shown to selectively fluoresce adenomatous tissue; however, these results are not consistent across all studies ( 29 ). In a study specific to endoscopic endonasal skull base surgery, 5-ALA was ineffective for the identification of neoplastic pituitary adenoma tissue ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation